2018
DOI: 10.23937/2469-5734/1510065
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multi-Functional Dental Cement for Enamel Remineralization and Anti-Cariogenic Bacteria Activity

Abstract: Fissure sealants are normally composite resin or glass ionomer cement (GIC) materials. In a systematic review [2] comparing the results of eight studies of composite resin-based and GIC-based sealants, three stud

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In our previous studies, we demonstrated that porous spherical-shaped HAp improved not only mechanical strengths [19,20,21,22,23], but also the release properties of fluoride and the other ions [19,20,21,22,23] as well as the antibacterial property [19,21,23] of conventional GICs. In previous studies [19,20,21,22,23], the amount of GIC glass powder was relatively reduced to mix HAp particles with the GIC glasses in the AIC group. In other words, the total powder/liquid ratio (P/L) between the sample groups was unified in the GIC-1.2 and AIC-0.9 groups in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous studies, we demonstrated that porous spherical-shaped HAp improved not only mechanical strengths [19,20,21,22,23], but also the release properties of fluoride and the other ions [19,20,21,22,23] as well as the antibacterial property [19,21,23] of conventional GICs. In previous studies [19,20,21,22,23], the amount of GIC glass powder was relatively reduced to mix HAp particles with the GIC glasses in the AIC group. In other words, the total powder/liquid ratio (P/L) between the sample groups was unified in the GIC-1.2 and AIC-0.9 groups in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This material is a porous and spherical-shaped hydroxyapatite (HApS), having less than 1/600 the strength of GIC glass particle, incorporated into conventional GIC. We suggest that HApS not only reinforced flexural and compressive strength, but also enhanced fluoride and the other ion release properties as well as the antibacterial property against cariogenic bacteria of conventional GIC [19,20,21,22,23]. However, the shear bond strength, fracture toughness, solubility, and acid buffer capability of AIC with HApS have not been examined; moreover, the reaction mechanism that led to the aforementioned effects by HApS has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%